(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This paper shows the state of the social capital between 2004 and 2014 in front of the implementation of the Mexican policy of attention to poverty. The investigation contemplates the beginning of the OPPORTUNIDAES program, and its passage to the PROSPERA program. The first study was conducted in a municipality in the state of Guerrero, and the second in the state of Oaxaca. The work made use of semi-structured interviews, face-to-face and with a mixed questionnaire, these were complemented with the observation technique to obtain a contextualized understanding of the situation at different explanatory levels. The results show that the policy of attention to poverty has a negative effect on the development of social capital. It was observed that the targeting method employed by these poverty attention programs creates two networks of social relationships, beneficiaries and non-beneficiaries; from the perspective of social capital, this influences the development of cooperation, solidarity, trust, reciprocity and social norms; that is, the fragmentation of social ties in a community has an impact on local development, and this does not counteract poverty.